Monitoring and characterization of cirrus clouds in Punta Arenas using lidar data. Study of latitudinal and hemispheric differences in cirrus cloud optical properties" - (:unkn) unknown (My University, 2025)
The main objective of the research proposal is to investigate the latitudinal and hemispheric differences in the optical properties of cirrus clouds. A Raman polarization lidar newly installed in September 2016 at the southern-midlatitude site of Punta Arenas (Chile) provides the first ever chance to characterize the cirrus clouds in this region. Also, give a chance to contrast the properties of cirrus clouds in the latitude band between 60 and 40°S to existing datasets from other regions. Such a study will not only aid to characterize regional differences in cirrus cloud properties, but also to investigate whether differences in the background aerosol load contribute to potential contrasts in cirrus cloud optical and geometrical properties. Southern South America is one of the last regions on Earth that can be considered pristine. If, at all, anthropogenic aerosols could influence the cirrus morphology in the strongly polluted northern midlatitudes, contrasts should be visible in the Punta Arenas datasets of pristine clouds. The relevance of the present proposal will be to study and characterize the cirrus clouds with a long term and unique dataset in a pristine site of the southern hemisphere. The obtained characteristics of cirrus clouds will be contrasted with the counterparts from other latitudes in South America and the northern hemisphere. The General Goal is Monitoring and characterizes the geometrical and optical properties of cirrus clouds in a pristine site of Punta Arenas, creating a good quality dataset to compare their properties with cirrus measured from other regions in South America and Northern Hemisphere. And Specific Goals are ? Adapt and apply existing algorithms for the retrieval of cirrus cloud optical properties to the new Punta Arenas lidar system described below, ? Adapt and apply previously adapted algorithm for Punta Arenas to process lidar signal of cirrus cloud from São Paulo and Natal in Brazil, ? Evaluate the acquired cirrus cloud dataset against existing cirrus studies from different regions. ? Perform a first discussion of possible aerosol effects on the observed cirrus properties in different regions. ? to conduct collocated measurements with LACROS lidar system during DACAPO – PESO to evaluate the quality of the measurements of SAVERNET lidar. ? perform measurements of the lidar parameters, in order to obtain a good quality dataset during the monitoring of the atmosphere and cirrus clouds. These objectives will help to answer key questions: Is there an observable difference between the properties of cirrus clouds in the southern midlatitudes compared against their northern hemisphere counterparts? Is there an observable difference between the properties of cirrus clouds in the southern midlatitudes compared against their Southern Hemisphere tropical and subtropical counterparts? To get these objectives and answer the scientific questions the lidar technique will be used. Aerosols backscattering and raman Lidar will be used to probe the atmosphere. Two lidars will be used, one installed permanently in Punta Arenas, SAVERNet lidar and the other will be installed during the measurement campaign DACAPO – PESO to obtain the properties of cirrus clouds. Also lidar information from Sao Paulo and Natal sites will be used to obtain the cirrus clouds properties from other sites in South America. Lidar onboard satellite information also will be used. Data from lidar in satellite will be used too, the lidar CALIOP onboard CALIPSO satellite. To study where cirrus clouds come from HYSPLIT backtrajectories model will be used. Inter-comparison between lidar instruments and CALIOP will be conducted to compare the instruments and cirrus clouds properties. A comparison between the cirrus clouds properties will be conducted in order to evaluate the differences between cirrus from different geographical regions. Finally we expect to obtain as results three papers in internationals scientific peer-reviewed, two theses of master degree and one these in doctoral degree. These results will enhance the promotion and expansion of the knowledge about cirrus clouds and the atmospheric science in our region and the world.